Pengaruh Girlband Itzy Sebagai Celebrity Endorser Terhadap Brand Awareness Susu Uht Ultramilk Pada Mahasiswa Ilmu Komunikasi UNJ Angkatan 2020 - Fauziyah, Hasna Nur; Anindhita, Wiratri; Nugrahaeni, Elisabeth (Innovative: Journal Of Social Science Research, 2025)
The progress of technology and the internet is progressing rapidly, there are many new things that can be done based on technology and the internet, this is also directly proportional to the development of marketing strategies which are also developing with the help of technology and the internet, starting from being a place to search for knowledge to becoming a tool. assist with the technical implementation of the strategy. Technology and internet. At this time Indonesia often hooked up Korean acts (Korean artists) to collaborate in the marketing industry, this is directly proportional to the increase in the Korean Wave (K-Wave) or Hallyu star phenomenon in Indonesia which is currently very popular with many teenagers in Indonesia, one of which is ITZY which has officially become Celebrity Endorser from Ultramilk UHT Milk. Ultramilk UHT Milk and ITZY collaborated to mobilize and introduce the hashtag #DontStopYoureMove. The method used is a quantitative method. The population in this research are students of the Jakarta State University Communication Science study program class of 2020. The results obtained in this research show that there is an influence between advertising on the YouTube platform on students' buying interest. This is proven by calculations using t count and t table as well as significance analysis, where the significance value shows results below 0.05 and the t count results are greater than t table. Apart from that, in this case Netflix advertisements on YouTube have a direct relationship with variable Y with a constant value of 11,313. Based on this, it can be concluded that the ITZY Girlband as a Celebrity Endorser has an influence on Brand Awareness of Ultramilk UHT Milk among UNJ Communication Science Students class of 2020